2006
DOI: 10.1017/s0265021505222111
|View full text |Cite
|
Sign up to set email alerts
|

The involvement of nitric oxide on the analgesic effect of tramadol

Abstract: References1. Metzler H, Gries M, Rehak P, Lang TH, Fruhwald S, Toller W. Perioperative myocardial cell injury: the role of troponins. Br J Anaesth 1997; 78: 386-390. 2. Raby KE, Goldman L, Creager MA et al. Correlation between preoperative ischemia and major cardiac events after peripheral vascular surgery. New Engl J Med 1989; 321: 1296-1300. 3. Christenson RH, Apple FS, Morgan DL et al. Cardiac troponin I measurement with the ACCESS immunoassay system: analytical and clinical performance characteristics. Cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…This is in accordance with Abd Zaher et al, 34 who reported that treatment with tramadol for several consecutive days resulted in an increase in levels of NO production in the brain. Furthermore, an inhibitory effect of NO on testosterone secretion by rat Leydig cells has been described by Dal et al 12 Rosselli et al 35 reported that excessive generation of NO under pathological conditions can reduce sperm motility by contributing to the formation of peroxynitrite, a highly toxic anion of peroxidation. This might help to explain the reduced sperm motility of tramadol-treated rats in the present study.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This is in accordance with Abd Zaher et al, 34 who reported that treatment with tramadol for several consecutive days resulted in an increase in levels of NO production in the brain. Furthermore, an inhibitory effect of NO on testosterone secretion by rat Leydig cells has been described by Dal et al 12 Rosselli et al 35 reported that excessive generation of NO under pathological conditions can reduce sperm motility by contributing to the formation of peroxynitrite, a highly toxic anion of peroxidation. This might help to explain the reduced sperm motility of tramadol-treated rats in the present study.…”
Section: Discussionmentioning
confidence: 93%
“…NO was postulated to be involved in the analgesic effect of tramadol. 12 The present study aimed to evaluate the effects of long-term tramadol treatment on testicular functions in adult male rats. In addition, an attempt to show the possible role of NO and oxidative stress in these effects will be undertaken.…”
Section: Introductionmentioning
confidence: 99%
“…Testicular tissues showed malformed (Abdellatief et al., ) and reduced number (Ghoneim, Khalaf, Elsamanoudy, & Helaly, ) of Leydig cells after chronic administration of tramadol. Furthermore, Dal et al., described a suppressing influence of nitric oxide (NO) on testosterone secretion by Leydig cells in rats (Dal et al., ). Evaluation of testicular tissue after 6 weeks of tramadol administration led to straight testicular atrophy resulting in low sperm density in the epididymal lumen, depressed motility and sperm structural aberrations (Azari et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Tramadol is one of the most effective prescriptions for treating pain (Ahmad et al., ; Awadalla & Salah‐Eldin, ). It is an opioid analgesic, modifies the pain centrally, through mu receptor agonistic action, and inhibiting serotonin and norepinephrine reuptake in neurons, and locally by increase in nitric oxide (NO) level (Dal, Salman, Salman, Iskit, & Aypar, ; Grond & Sablotzki, ; Oliva et al., ). O‐desmethyl‐tramadol, an active tramadol metabolite, is 2–4 times as potent as tramadol (Grond & Sablotzki, ; Matthiesen, Wohrmann, Coogan, & Uragg, ; Tao et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…It was recently demonstrated that during spinal nociceptive processing, cGMP produced by NO–GC may activate signalling pathways different from those activated by PKG‐I 67 . Different studies have demonstrated the implications of the NO–cGMP pathway in the analgesic effect of several drugs that are indicated for the treatment of neuropathic pain, such as tramadol, 68 spinal‐administered clonidine, 69 gabapentin 70,71 and also in the anti‐nociceptive effect of anti‐inflammatory drugs such as indomethacin, 72 and in the hyperalgesia induced by intrathecal high‐dose morphine 73 . It has been suggested that the analgesic effect of one of the most popular drugs in the pain treatment, paracetamol (acetaminophen), is partially mediated through the inhibition of NO generation 74 .…”
Section: The No–cyclic Guanosine Monophosphate (Cgmp) Pathwaymentioning
confidence: 99%